Pelvic inflammatory disease: clinical feature, risk factors, treatment, and prevention - Mohamed, Abdelrahim Awadelkarim Abdelrahman (Indian Journal of Community Health, 2024)
Pelvic Inflammatory Disease (PID) is a significant public health concern with severe repercussions for reproductive health, including ectopic pregnancies, chronic pelvic pain, and tubal infertility. This study provides a comprehensive examination of PID, covering its clinical characteristics, risk factors, etiological agents, diagnostic methods, treatment options, and preventive strategies. PID encompasses a variety of inflammatory disorders of the upper female genital tract caused by pathogens such as Neisseria gonorrhoeae, Chlamydia trachomatis, vaginal flora, and other bacteria. Despite a decline in PID cases associated with N. gonorrhoeae and C. trachomatis, these pathogens remain substantial contributors. Key risk factors include age under 25, multiple sexual partners, unprotected sex, early sexual debut and a history of sexually transmitted diseases (STDs) or previous PID. Diagnosis relies primarily on clinical evaluation, with symptoms ranging from mild pelvic discomfort to severe abdominal pain, complicating timely diagnosis. Effective treatment involves the use of empirical broad-spectrum antibiotics. Preventive strategies emphasize early detection and treatment of STIs, adherence to screening guidelines, and measures to prevent recurrent PID episodes. Effective management of PID requires early detection, prompt intervention, and comprehensive preventive measures targeting both initial and recurrent cases. Adherence to STI screening and treatment protocols is crucial in reducing PID incidence and associated complications. Continued research is vital to enhance the understanding of pathogenic mechanisms and optimize treatment protocols, thereby improving the quality of life for women affected by PID.